Interpersonal Communication and Customer Satisfaction: Evidence from a Premium Café in Surabaya - Edson Abrar Rasendria Prabaswara; Hilda Yunita Wono (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of cafes in Surabaya has led to intense competition, making high-quality service and pleasant communication essential. This study examines the effect of employee interpersonal communication on customer satisfaction at Toby’s Estate Pakuwon Mall Surabaya. The population includes all customers who have directly interacted with employees, with a sample of 100 respondents selected through purposive sampling based on age, visit frequency, direct interaction, willingness to participate, and residence. Data were collected using online questionnaires and analyzed with simple linear regression in SPSS. Results indicate that interpersonal communication has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.553, significance value of 0.028, and coefficient of determination of 0.804. Descriptive analysis showed a mean score of 4.335 in the strongly agree category. Findings confirm that interpersonal communication is a key factor in enhancing customer satisfaction in premium cafes.